PENGARUH TATA KELOLA PERUSAHAAN, TRANSFER PRICING, DAN LEVERAGE TERHADAP TAX AVOIDANCE - FRANSISCA ADELIA PUSPITA; RUTJI SATWIKO (E-Jurnal Manajemen Trisakti School of Management (TSM), 2026)
The purpose of this study is to obtain empirical evidence regarding the influence of independent variables on the dependent variable. This study uses seven independent variables: Managerial Ownership, Institutional Ownership, Foreign Ownership, Board Gender Diversity, Independent commissioners, Transfer pricing, and leverage. The dependent variable in this study is tax avoidance. The sample used in this study is 395 data from manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2022-2024. The method used in this study is purposive sampling. This study uses multiple regression to analyze the data. The results of this study indicate that Board Gender Diversity and Transfer pricing variables have an effect on tax avoidance. Meanwhile, Managerial Ownership, Institutional Ownership, Foreign Ownership, Independent commissioners and leverage have no effect on tax avoidance.